2022
DOI: 10.1007/s11524-022-00628-4
|View full text |Cite
|
Sign up to set email alerts
|

Examining Associations between Adverse Childhood Experiences and Posttraumatic Stress Disorder Symptoms among Young Survivors of Urban Violence

Abstract: Our study examines the association between Adverse Childhood Experience (ACE) exposure and posttraumatic stress disorder (PTSD) symptoms among survivors of violence. In this cross-sectional study, an ACE questionnaire and PTSD Checklist for DSM-5 (PCL-5) were completed by 147 participants ≤ 3 months after presenting to a Philadelphia, PA emergency department between 2014 and 2019 with a violent injury. This study treated ACEs, both separate and cumulative, as exposures and PTSD symptom severity as the outcome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These interaction effects are likely to be more pronounced among patients with a violently injury. Research has found that 50% to 57% 2,22 of patients with a violent injury report four or more adverse childhood experiences, which is associated with an increased risk of mental and physical health problems, 23 compared with only 11% of patients who experienced a motor vehicle collision or severe burn 24 . These complex circumstances may overwhelm some individuals' ability to cope effectively after they are violently injured and make it challenging for them to seek out and engage in mental health resources like TRRP without support (e.g., referrals, appointment reminders, transportation).…”
Section: Discussionmentioning
confidence: 99%
“…These interaction effects are likely to be more pronounced among patients with a violently injury. Research has found that 50% to 57% 2,22 of patients with a violent injury report four or more adverse childhood experiences, which is associated with an increased risk of mental and physical health problems, 23 compared with only 11% of patients who experienced a motor vehicle collision or severe burn 24 . These complex circumstances may overwhelm some individuals' ability to cope effectively after they are violently injured and make it challenging for them to seek out and engage in mental health resources like TRRP without support (e.g., referrals, appointment reminders, transportation).…”
Section: Discussionmentioning
confidence: 99%
“…People who experience more adverse events during childhood are more likely to develop chronic illnesses such as heart disease, respiratory disease, and cancer [4]. Also, they are susceptible for developing depression, anxiety, and posttraumatic stress disorders [5][6][7]. The reasons why adverse childhood events may lead to poor health are diverse and still not completely understood, but sustained activation of the stress response system is assumed to be at the heart of this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, early‐life adversity has been associated with a greater mental health burden in adolescence and early adulthood (Gilbert et al., 2009) as well as earlier onset of mental illness (McLaughlin et al., 2012). Numerous cross‐sectional studies report that maltreated or stress‐exposed children have higher depressive and anxiety symptoms (Dunn, Nishimi, Powers, & Bradley, 2017; Kim, Jang, Chang, Park, & Lee, 2013), behavioral problems (Yates, Dodds, Sroufe, & Egeland, 2003), posttraumatic experiences (Tabb et al., 2022), and suicidal ideation (Afifi et al., 2008). These findings have been replicated in a longitudinal study which found that early‐life adversity is associated with higher depressive symptoms, suicidality, and comorbid anxiety (Klein et al., 2009).…”
Section: Introductionmentioning
confidence: 99%